أثر إستراتيجية العصف الذهني في تنمية مهارات التعبير الكتابي الإبداعي لدى طلبة الصف التاسع الأساسي في الأردن - عطالله، أسماء سليمان توفيق; عبابنة، إيمان عبدالفتاح (الجامعة الأردنية - عمادة البحث العلمي, 2019)
This study aimed at investigating the effect of using brain storming strategy in the developing of creative written expression skills of the ninth grade students in Jordan. The sample of the study consisted of (120) male and female students, distributed equally over two groups: An experimental, taught through brain storming strategy, and a control group. They intentionally selected from Jubayhah Secondary School for Boys and Caesarea Elementary School for Girls in the academic year 2014/2015. The researchers conducted pretest and posttest. The findings of the study showed that there were statistically significant differences at the level (0.05 ≤ α) between the experimental group and the control group in the total score and the sub scores of the creative written expression skills in favor of the experimental group, and significant differences attributed to sex variable. No significant differences were indicated due to the interaction between the teaching strategy and gender of the student on creative written expression skills. The researchers recommended to use of this strategy in the schools as well as conducting more studies regarding its effect by using other samples in different environments.
هدفت الدراسة إلى معرفة أثر استراتيجية العصف الذهني في تنمية مهارات التعبير الكتابي الإبداعي لدى طلبة الصف التاسع الأساسي في الأردن، وتكون أفراد الدراسة من (120) طالبا وطالبه موزعين على مجموعتين إحداهما ضابطة مكونة من (60) طالبا وطالبه، وأخرى تجريبية مكونة من (60) طالبا وطالبه من طلبة الصف التاسع الأساسي لسنة 2015/2014، واختيرت بصورة قصدية من المدارس التابعة للواء الجامعة هما مدرسة الجبيهة الثانوية للبنين، وقيساريا الأساسية للبنات، واختيرت الشعب منها بشكل عشوائي، وتم تدريس المجموعة التجريبية وفق استراتيجية العصف الذهني، أما المجموعة الضابطة فقد درست وفقا لطريقه الاعتيادية، ولتحقيق أهداف الدراسة استخدم اختبار قبلي وبعدي. وأظهرت النتائج تفوق المجموعة التجريبية في مهارات التعبير الكتابي الإبداعي بدلالة إحصائية عند مستوى (0.05 ≤ α) على المجموعة الضابطة تعزي لمتغير الاستراتيجية، ووجود فروق بين المجموعتين تعزى إلى الجنس، وعدم وجود فروق بين المجموعتين تعزى إلى التفاعل بين الاستراتيجية والجنس، لذلك فقد أوصت الباحثتان بضرورة استخدام استراتيجية العصف الذهني في تدريس التعبير الكتابي الإبداعي.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- المهارات التعليمية -- مهارات التعبير الكتابي -- التعليم الأساسي -- طلاب مرحلة الأساس -- الإستراتيجية التعليمية -- العصف الذهني -- مستخلصات الأبحاث